(untitled) (AYUSHDHARA, 2023)
The prevalence rate of generalized anxiety disorder is increasing constantly in the modern era. In Ayurveda, the symptoms of this disease show a resemblance with the condition called Cittodvega (excited state of mind), which is one among the Manovikara in Ayurveda caused by dysfunction of increased Vata and Pitta dosha. The present study was conducted as a clinical trial to study the effect of Smriti meditation on ten diagnosed participants of generalized anxiety disorder within the age group of 18–60 years selected from the Manassanthi outpatient department of VPSV Ayurveda college, Kottakkal. 3-5 sessions of smriti meditation for 1-2 hours were done for all the participants within 15 days, and the follow-up assessment was done 1 week after the last meditation session. The Smriti meditation technique is an interactive guided psychotherapeutic meditation technique derived from the descriptions of Satvavavjaya chikitsa mentioned in Caraka Samhita. Assessment scores of different intervals were statistically analysed using repeated measures analysis of variance. Based on the results, it was found that smriti Meditation has a statistically significant effect in reducing the symptoms of all the domains of the Hamilton anxiety rating scale and also improves the quality of life of participants within a short period.